Caspase Cascade Activation During Apoptotic Cell Death of Human Lung Carcinoma Cells A549 Induced by Marine Sponge Callyspongia aerizusa - Hadisaputri YE; Andika R; Sopyan I; Zuhrotun A; Maharani R; Rachmat R; Abdulah R (Dove Medical Press, 2021)
Yuni Elsa Hadisaputri,1,2,* Rheza Andika,1,2,* Iyan Sopyan,3 Ade Zuhrotun,1 Rani Maharani,2,4 Rachmaniar Rachmat,5 Rizky Abdulah6 1Department of Pharmaceutical Biology, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, Indonesia; 2Division of Biological Activity, Central Laboratory, Universitas Padjadjaran, Jatinangor, Indonesia; 3Department of Pharmaceutical and Pharmacy Technology, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, Indonesia; 4Department of Chemistry, Faculty of Mathematic and Sciences, Universitas Padjadjaran, Jatinangor, Indonesia; 5Oceanographic Research Center, Indonesian Institute of Sciences, Jakarta, Indonesia; 6Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, Indonesia*These authors contributed equally to this workCorrespondence: Yuni Elsa HadisaputriDepartment of Pharmaceutical Biology, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Bandung-Sumedang KM.21, Jatinangor, West Java, 45363, IndonesiaTel +62-22-84288888 Ext. 3510Email yuni.elsa@unpad.ac.idIntroduction: In this study, Callyspongia aerizusa (CA), one of the most popular marine sponges for cancer therapy research, was investigated for its phytochemical compounds and evaluated for its anticancer activity in various cell lines. Since lung cancer is the most frequently diagnosed cancer, a solution from this marine source is a good choice to address the resistance to anticancer agents. Elucidation of the underlying mechanism of cell death elicited by a CA extract in human lung carcinoma cells A549 was undertaken.Methods: The presence of secondary metabolites in CA methanol extract was revealed by gas chromatography-mass spectrometry (GC-MS) and evaluated on four cancerous cell lines and a non-cancerous cell line using Cell Counting Kit-8. Since the activity of CA extract in A549 cells was then evaluated through clonogenic assay, morphological detection of apoptosis, polymerase chain reaction (PCR) and Western blot assay, were also presented in this study.Results: GC-MS analysis revealed the presence of two ergosteroids, ergost-22-en-3-one, (5β,22E), and ergost-7-en-3-ol, (35β) in the sponge extract that was suggested to suppress A549 cells (IC50 9.38 μg/mL), and another cancerous cell’s viability (IC50 3.12– 10.72 μg/mL) in 24 h, but not in the non-cancerous cells. Moreover, CA extract was also able to reduce the colony-forming ability of A549 cells, and through A549 cells morphology seems that apoptosis is the underlying mechanism of cell death. Further, the treatment with CA extract induced the up-regulation of caspase-9, caspase-3, and PARP-1, and the down-regulation of BCL-2, in both mRNA and proteins expression level, promoting apoptotic cell death via caspase cascade.Conclusion: These findings suggest that the compounds in CA extract possess the ability to induce apoptotic cell death in A549 cells and could become a promising candidate for future anticancer therapy.Keywords: Callyspongia aerizusa, ergosteroids, lung cancer, A549, apoptosis